MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. Issue 1 (December 2016) - Eldomery, Mohammad; Akdemir, Zeynep; Vögtle, F.-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini; et al.
Abstract Background Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. Methods Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organismSaccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. Results Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) inMIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includesMIPEP . All amino acids affected in the patients' missense variants are highly conserved from yeast to human and thereforeS. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. Conclusions Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.